Pengaruh Customer Satisfaction, Calculative Commitment, dan Corporate Image terhadap Attitudinal Loyalty dan Behavioral Loyalty Pada Program Pasti Prima Pertamina (Studi Pada SPBU Pasti Prima Wilayah Jakarta) - Rahma Sri Handayani; Citra Kusuma Dewi (Jurnal Sekretaris dan Administrasi Bisnis, 2020)
This research is motivated by a previous observation result which show that customer satisfaction in using Pertamina's gas station services has been stagnant for the past several years. From these results, Pertamina created the latest gas station program namely "Pasti Prima" which is a concept with the aim of increasing customer’s satisfaction in using Pertamina's services and products. This study aims to determine the impact of Customer Satisfaction, Calculative Commitment, Corporate Image on Behavioral Loyalty through Attitudinal Loyalty as a Stepwise variable model. This research uses quantitative methods and uses descriptive and causal research types. We collect the data using questionnaires that we have distributed at certain SPBU Pasti Prima gas stations in Jakarta. We took the sample data using non-probability sampling method with incidental sampling type to 100 respondents. Then Descriptive Analysis and Partial Least Square (PLS) analysis are used as data analysis techniques. Before conducting PLS analysis, the data was transformed using the Statistical Interval Method (MSI) to convert ordinal data into intervals data. The results of this study indicate that Customer Satisfaction has a positive and significant impact on Attitudinal Loyalty, Calculative Commitment does not have a positive and significant impact on Attitudinal Loyalty, Corporate Image has a positive and significant impact on Attitudinal Loyalty, and Attitudinal Loyalty has a positive and significant impact on Behavioral Loyalty.